2006
DOI: 10.1108/09526860610686980
|View full text |Cite
|
Sign up to set email alerts
|

Evidence‐based re‐engineering: re‐engineering the evidence

Abstract: This appears to be the first time available evidence about redesign projects in hospitals has been systematically collected and assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 88 publications
0
10
0
Order By: Relevance
“…While this design can provide useful insights, it has serious limitations regarding generalizability and inter-subjectivity. Along with the other methodological issues surrounding the evaluation of lean thinking, which we mentioned in the introduction [ 7 ], it is safe to say that not only more research, but also higher quality research is needed. At this time, to state that ‘the lean message is 100% positive’ [ 17 ] seems a bit of a stretch.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While this design can provide useful insights, it has serious limitations regarding generalizability and inter-subjectivity. Along with the other methodological issues surrounding the evaluation of lean thinking, which we mentioned in the introduction [ 7 ], it is safe to say that not only more research, but also higher quality research is needed. At this time, to state that ‘the lean message is 100% positive’ [ 17 ] seems a bit of a stretch.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, a recent review identified only a few studies with a controlled before–after study design. To make matters worse, a wide range of often non-comparable measures was used, while some of the reported results were not even mentioned in the objective of the study and vice versa [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although research shows that transition to process orientation besides reducing cost also lead to a more patient-centred care and quality improvements, [20,21] in reality, according to a review of 86 studies on innovations related to re-engineering patient care, the dominant motivator for initiation of these changes was cost reduction and resource utilisation, while parameters related to patient experience and patient values were rarely used. [22] Therefore, the Latvian case while being a rather extreme example of the forced change, is however typical regarding the main motivator behind it. Respectively, by exploring the differences in adaptation in Latvian hospitals exposed to the same external environmental changes, the best practices used for process management implementation in clinical setting could be detected and further applied in other hospitals moving towards HPO.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies also report better patient outcomes after a redesign project. However, there are also various gaps in redesign literature [3,8,9]. One of these gaps is that very few research papers have investigated the effects of redesign on areas of performance outside the timely delivery of services or better patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…'Redesign' is the general term for a group of approaches that is being used to achieve some of these improvements [2]. In redesign, one implements multifaceted organizational interventions that lead towards more customerfocused and cost-effective care, by removing unnecessary steps and potential for errors [3,4]. In a typical redesign project, operational improvements are accompanied by efforts to educate and activate the workforce, leadership support and other types of interunit coordination (sociotechnical improvements) [5].…”
Section: Introductionmentioning
confidence: 99%